Pain manifestations in nursing professionals: a scoping review - de Melo Oliveira, Sabrina; de Lima Ferreira, Larissa; Araújo da Silva, Thaís; da Silva Frazão, Iracema (Investigación y Educación en Enfermería, 2025)
Objective. To map the literature on the prevalence of pain in nursing professionals. Methods. This is a scoping review that was conducted according to the Joanna Briggs Institute (JBI) methodology for scoping reviews, and according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The protocol was developed and registered in the Open Science Framework (OSF) [https://osf.io/2zu73/]. The search was carried out in the following databases: PubMed/MEDLINE, Virtual Health Library (VHL), Web of Science, Scientific Electronic Library Online (SciELO), SciVerse Scopus, Embase, and the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES). Results. A total of 49 studies were included, all of which were cross-sectional studies, and the total sample of the included studies was 35,069 participants. Most of the included studies were concentrated in the Asian continent (71.4%). Among the selected studies, it was shown that the most affected area was the lumbar region (81.57%), followed by the neck (71.5%) and shoulder (31.57%) regions. Conclusion. According to the studies evaluated, the prevalence of occupational pain in nursing professionals was of musculoskeletal origin. The high prevalence of pain found reinforces the importance of monitoring the health of nursing workers.